TOOLS FOR DEVELOPING A STRATEGY FOR THE DEVELOPMENT OF REGIONAL AGRICULTURAL PRODUCTION - Elov, Dilshod; Olimjanova, Shoira; Jannazarova , Gauhar (International Journal of Psychosocial Rehabilitation, 2020)
he article substantiates the position that the development strategy of agricultural production is part of a comprehensive program of socio-economic development of territories. It developed a methodological approach to developing a strategy for the development of regional agro-industrial production, which involves assessing the starting conditions and economic prerequisites for development, due to regional factors, as well as the influence of external conditions.